Multidimensional Networking Behavior in Germany and China: Measurement Invariance and Associations With Objective Career Success. (November 2018) - Volmer, Judith; Orth, Maximilian; Wolff, Hans-Georg
Prior research has so far established the multidimensional nature of networking behavior in Western but not Asian working populations. Thus, the purpose of the present study was to assess the cross-cultural measurement equivalence and predictive validity of an established multidimensional networking scale across a German and a Chinese sample of individuals employed by the same multinational company (total N = 248). Multigroup confirmatory factor analyses demonstrated configural and metric, but not scalar measurement invariance, indicating that cross-cultural comparisons of associations between the six theoretically anticipated networking dimensions and other constructs but not of mean scores of networking are meaningful. Path analytic findings showed that some but not all networking dimensions significantly predicted objective career success (i.e., salary and promotions, assessed 2 months later). Relative weight analyses indicated that all intraorganizational (i.e., building, maintaining, and using contacts), but no extraorganizational networking behaviors explained nontrivial variance in Chinese employees' salary and promotions. In the German group, a largely opposite pattern was found. Interestingly, the relative importance of building and of using internal contacts was significantly greater in China than in Germany. We conclude that the functional but not necessarily the structural facet of a multidimensional conceptualization of networking behavior exhibits meaningful cross-cultural equivalence.